Միգրացիան և անվտանգությունը համաշխարհայնացման համատեքստում - Առաքելյան, Իռա (Լիմուշ հրատ.)
This article considers the impact of globalization as a source of qualitatively new transformations, new problems, and contradictions of the present-day world on the development of modern migration, and its impact on security. Globalization is analyzed as a phenomenon integral to the current stage of civilization development. International migration reflects all the most critical problems that accompany the current process of globalization. Migration poses real or potential risks to almost any aspect of security. The global nature of the new world order must reflect the three fundamentals of peace: security; social and economic well-being and development; democracy and respect for human rights and freedoms.
Keywords: Սոցիոլոգիա